Peran Garuda Institute Dalam Pemberdayaan Perekonomian Kampung Buricak Burinong - Rohman, Encep Ab; Lathief, Afief Abd; Aziz, Ali (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
The purpose of this research is to find out more about the Economic Empowerment program implemented by the Garuda Institute for the people of Pakualam Village, to find out about the ongoing activity processes and the results that are obtained or felt by the community after the Buricak Burinong Village program was implemented. The research method used is descriptive method with a qualitative approach. The results of this study are: first the program implemented by the Garuda Institute in the form of Colorful Village, Processed Product Training and Culinary Tourism of Buricak Burinong Village, with the first activity process looking at environmental conditions first, second looking at the level of education and community potential, and third looking at the economic condition of Pakualam Village then tries to collaborate between the natural potential and the potential of the community with the economic conditions of the community and the results obtained.